2014
DOI: 10.1016/j.toxrep.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the nutritional and toxicological reference values of trace elements in edible marine fish species consumed by the population in Rio De Janeiro State, Brazil

Abstract: The present study estimated the human daily and weekly intake of inorganic elements due to consumption of fish in Rio de Janeiro state and the associated potential health risks posed by some toxic elements. All samples analyzed had values of Cd and Pb below the Maximum Tolerable Limits of 3.0 mg kg−1 for Pb and 1.0 mg kg−1 for Cd; only Mugil cephalus, Cynoscion leiarchus and Caranx crysos had As concentrations below 1 mg kg−1, maximum limit established by Brazilian legislation. The higher values of Cd and Pb c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 25 publications
(43 reference statements)
0
3
2
Order By: Relevance
“…[42], stated that the mean Pb concentration from C. nigrodigitatus, E. fimbriata and P. elongatus in the Cross-river system, Nigeria was 3.0mg/kg, 3.8 mg/kg and 10.0 mg/kg respectively. The mean Pb levels in fish muscles in this study, (0.14 -0.48 Mg/g) were observed to be greater than those in the studies conducted by [43,44]. The average Pb levels in the fish muscles in this present study is lower compared to other studies as shown in Table 3.…”
Section: Leadcontrasting
confidence: 74%
See 1 more Smart Citation
“…[42], stated that the mean Pb concentration from C. nigrodigitatus, E. fimbriata and P. elongatus in the Cross-river system, Nigeria was 3.0mg/kg, 3.8 mg/kg and 10.0 mg/kg respectively. The mean Pb levels in fish muscles in this study, (0.14 -0.48 Mg/g) were observed to be greater than those in the studies conducted by [43,44]. The average Pb levels in the fish muscles in this present study is lower compared to other studies as shown in Table 3.…”
Section: Leadcontrasting
confidence: 74%
“…Whereas As level in C. gariepinus and S. shchall were below the maximum permissible limit set by [46]. Generally, the As concentrations in the muscle of the three fish species were higher compared to the values reported by [43], but lower than values reported in other literatures (Table 3). Chinese Health Ministry 0.1 0.1 0.5 [46] World Health Organization 1.00 30 2.0 0.5-1 100 [39] Codex Alimentarius Commission 0.3 [48] (Modified from [50])…”
Section: Arseniccontrasting
confidence: 56%
“…2018). The RfD value for As is given as the amount of inorganic As, that are known to be estimated as 10% of total As (Afonso et al 2013;Medeirosa, Gobbo dos Santos, Goncalves, Bahia Braga, Krauss & do Couto Jacob. 2014).…”
Section: Risk Assessments For Healthmentioning
confidence: 99%
“…However, fish is one of the major sources of protein in the world, containing essential fat, vitamins, and minerals [ 5 ]. The world per capita fish supplies have increased from 18.1 kg in 2009 to about 20.3 kg in 2016 [ 5 , 6 ]. On the other hand, the intake of fish in Malaysia has surprisingly increased by at least 150% from 1961 to date.…”
Section: Introductionmentioning
confidence: 99%